The Effect of Flipped Classroom on Students’ Learning Style, Intrinsic Motivation and Learning Achievement - Ni Kadek Sepriani; Alberth Alberth; Nurnia Nurnia (Journal of Language Education and Educational Technology (JLEET), 2022)
The main objective of the study was to examine the effect of flipped classroom on students' learning styles, intrinsic motivation and learning outcomes. The sample consisted of 37 students enrolled in the Teacher Training Faculty, Halu Oleo University during the 2018/2019 academic years, recruited through a purposive sampling technique. The study employed the VAK learning style questionnaire consisting of 30 questions and the intrinsic motivation questionnaire, based on the Self-Determination Theory comprising 17 questions. Learning achievement was measured using a learning achievement test consisting of 35 questions. The instruments were administered twice: a pre-test to determine students' prior learning style, intrinsic motivation, and achievement, and a post-test to assess whether changes occurred. The results showed significant changes in students' learning style, as demonstrated by the two-tailed score of the Pearson correlation test (p < 0.05). The analysis also revealed a significant effect of the flipped classroom on students' intrinsic motivation, with a two-tailed significance score of 0.045. Paired sample t-tests indicated a significant effect of the flipped classroom on students' learning achievement, as evidenced by changes in scores from pre- to post-test. In conclusion, this study demonstrated that the flipped classroom model has a significant effect on students' learning style, intrinsic motivation, and learning achievement.